Ebola epidemic exposes the pathology of the global economic and political system. (October 2015) - Sanders, David; Sengupta, Amit; Scott, Vera
While the current Ebola epidemic spiraled out of control to become the biggest in history, the global public health response has been criticized as "too little, too late." Many, like the World Health Organization, are asking what lessons have been learned from this epidemic. We present an analysis of the political economy of this Ebola outbreak that reveals the importance of addressing the social determinants that facilitated the exposure of populations, previously unaffected by Ebola Virus Disease, to infection and restricted the capacity for an effective medical response. To prevent further such crises, the global public health community has a responsibility to advocate for health system investment and development and for fundamental pro-poor changes to economic and power relations in the region.